Antioxidant, α-amylase and acetylcholinesterase inhibitory potential of Mazus pumilus (Japanese Mazus) extract: An in-vitro and in-silico study - Saheem Ahmad; Sultan Alouffi; Uzma Shahab; Naif K. Binsaleh; Mohamed E. Ghoniem; Rihab Akasha; Mohammad Kaleem Ahmad; Naved Ahmad; Mohd. Waiz; M. Salman Khan (Arabian Journal of Chemistry, 2024)
Plant-derived secondary metabolites possess diverse biological activities that are beneficial to humans. Modern medications used for diabetes and Alzheimer’s often cause side effects, prompting reliance on traditional alternatives. Therefore, we aimed to uncover the potential of Mazus pumilus in countering diabetes and Alzheimer’s by in-vitro inhibition of α-amylase and AChE. Additionally, antioxidant activity and phytochemical analyses were performed. Mazus pumilusThe plant was extracted sequentially using n-hexane, ethyl acetate, dichloromethane, methanol, and water. The methanolic fraction, notably, manifested marked antioxidant efficacy against DPPH and ABTS radicals. Subsequently, this extract evinces noteworthy inhibitory attributes against α-amylase and AChE, respectively, in a competitive manner. Moreover, the bioactive phytoconstituents present in the methanolicextracts were determined through GC–MS analysis, and subsequent computational molecular docking studies revealed that these compounds strongly bound to the active site of both α-amylase and AChE. The calculated least binding energies, for α-amylase and AChE, underscore the viability of the molecular interactions. In conclusion, the antioxidant, antidiabetic, and anti-Alzheimer attributes of Mazus pumilus extract likely emanate from the synergistic interplay of its bioactive phytoconstituents. A comprehensive in-vitro and in-vivo study is essential to fully explore the anti-diabetic and anti-Alzheimer potential of secondary metabolites of Mazus pumilus.